PENCEMARAN NAMA BAIK OLEH PERS DI ERA MEDIA SIBER SUATU KAJIAN PERTANGGUNGJAWABAN PIDANA - Ni Gusti Agung Ayu Mas Tri Wulandari; I Gusti Ayu Eviani Yuliantari (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
The cyber media phenomenon has had a major impact on the world of the press, both in terms of access to information and in maintaining journalistic integrity. However, this phenomenon also brings new challenges, especially regarding acts of defamation by the press through cyber media. This raises questions regarding the criminal liability that must be borne by the press in these cases. Using normative legal research methods, the author analyzes relevant laws and regulations, including the Press Law, ITE Law, and general criminal law. In this research, the author reviews various relevant laws and regulations and presents case study analysis related to hoaxes, radicalism and insults on social media. The research results show the need for more effective efforts in dealing with press crimes that harm the reputation and good name of individuals or groups. From the conclusions drawn, it appears that criminal liability for acts of defamation by the press in the context of cyber media is a complex issue. The need for revision and improvement of related laws and regulations, increased supervision and enforcement of the law, as well as public awareness and legal literacy are the suggestions proposed in this article.